Analytical formulation of the contact pressure evolution for interference joints under creep regime. (August 2020) - Esposito, L.; Bruno, M.; Bertocco, A.
Abstract: An analytical formulation to evaluate the contact pressure evolution in interference fit joints working under high temperature regime, is proposed. The phenomenon is mainly due to the stress relaxation related to the creep behaviour of materials used to realize this kind of joints. Despite extensive researches on the topic, the decay of contact pressure due to creep relaxation is commonly not considered or evaluated only by numerical methods. The proposed analytic solution correlates the contact pressure to the creep material properties and could be largely used to improve the design or the fitness-for-service assessment of joints that transmit load thanks to the interference fit. The formulation assumes the plane strain condition for the inner element and the plane stress condition for the outer one. It was validated by finite element analysis (FEA) and gives accurate prediction of the contact pressure evolution both in plane and axisymmetric simulations. Graphical abstract: Image 1 Highlights: An analytical formulation to evaluate the contact pressure evolution in interference fit joints subjected to elevated temperature, was presented. The formulation gives a clear correlation between the contact pressure decay and the creep properties of joined materials. The method is relatively simple yet reliable for load transmission assessment of interference-fit joints under creep regime.